Ingestão acidental de moedas por crianças: atuação do Setor de Otorrinolaringologia do Hospital João XXIII - T-ping, Cheng [UNIFESP] (2006)
The ingestion of foreign bodies by children is frequently seen in emergency departments. ENTs can manage those lodged in the esophagus but experience is important for a successful intervention. AIM: Describe seven cases of children that ingested coins, managed at the ENT Department of João XXIII Hospital. STUDY DESIGN: Clinical/prospective. MATERIALS AND METHODS: We describe seven cases (gender, age, family status, coin size and treatment/evolution). RESULTS: Age ranged from one to nine years. Two patients were only children and five were the youngest in their families. Coins sizes ranged from 1.9 to 2.5 cm. After eight hours of observation, three cases were treated in the surgery room because the foreign body was lodged in the cricopharynx. Four cases resolved spontaneously. CONCLUSION: The ENT department has good results removing coins lodged in the upper esophagus using forceps and laryngoscopy; and also using rigid esophagoscopy for the lower esophagus. In this study it was not possible to establish the importance of coin size and patient age in attempting to predict spontaneous resolution, nor if the child being an only child or the youngest in the family may have some predisposition in this kind of accident.